Studying The Rate Equation of Transversely Excited Atmospheric(TEA-CO2) Laser - ØµØ§ØØ¨ Ù†Ø¹Ù…Ø© Ø¹Ø¨Ø¯ Ø§Ù„ÙˆØ§ØØ¯; Ù‡Ù†Ø§Ø¡ ØØ³Ù† ÙƒØ§Ø¸Ù… (Al-Qadisiyah Journal of Pure Science, 2017)
This study depends on the soluting of non linear differential equations the rate equations of TEA- CO2 laser rate equation to accomplished the following:-calculating (laser power, intensity of laser beam, population differences between upper and lower laser levels and electrical input power) with time by using mixture (1:1:8) (CO2:N2:He)in TEA-CO2laser.The effect of TEA-CO2 laser pulse with following parameters (power, intensity, gain, population different and electrical input power) have been studied . All Mathematical relation have been studied with the following (power, intensity, loss energy, output energy , amplification coefficient , population differences between upper , lower laser levels, electron density and total energy).The result of researchØŒ showed that the electrical input power resulted by electrical discharge increases with time , through which we can notice the behavior of the current and voltage pulses and obtain typical designs for this type of laser and study the population of the upper and lower levels of laser.